The public university in Brazil: between academic ideals and government attacks (Research, Society and Development, 2022)
In Brazil, higher education is a diversified level of education, either by the type of institution, by the administrative dependence, by the regional issue or by the agents involved in it. We are interested in demarcating the predominance of private higher education institutions, which are notified of teaching, to the detriment of public higher education institutions, universities with a social function based on the indissociability between teaching, research and extension. Our objective is to discuss the different conceptions of higher education from the public-private dichotomy. This is a theoretical essay, bibliographic research focusing on international guidelines. The academic essay analyzes the emerging antagonisms of the higher education perspectives of the United Nations Educational, Scientific and Cultural Organization (Unesco) and the World Bank, identifies their forms of supply as a relevant marker to understand such dichotomy and highlights the recent scenario of attacks on public universities concomitant with the expansion of the private sector. Thus, we corroborate the theses about the consolidation of the commodification of higher education to the detriment of its universalization through the public university.